Herbivorous protist growth and grazing rates at in situ and artificially elevated temperatures during an Arctic phytoplankton spring bloom - Susanne Menden-Deuer; Caitlyn Lawrence; Gayantonia Franzè (PeerJ, 2018)
To assess protistan grazing impact and temperature sensitivity on plankton population dynamics, we measured bulk and species-specific phytoplankton growth and herbivorous protist grazing rates in Disko Bay, West Greenland in April-May 2011. Rate estimates were made at three different temperatures in situ (0 °C), +3 °C and +6 °C over ambient. In situ Chlorophyll a (Chl a) doubled during the observation period to ∼12  µg Chl a L−1, with 60–97% of Chl a in the >20 µm size-fraction dominated by the diatom genus Chaetoceros. Herbivorous dinoflagellates comprised 60–80% of microplankton grazer biomass. At in situ temperatures, phytoplankton growth or grazing by herbivorous predators <200 µm was not measurable until 11 days after observations commenced. Thereafter, phytoplankton growth was on average 0.25 d−1. Phytoplankton mortality due to herbivorous grazing was only measured on three occasions but the magnitude was substantial, up to 0.58 d−1. Grazing of this magnitude removed ∼100% of primary production. In short-term temperature-shift incubation experiments, phytoplankton growth rate increased significantly (20%) at elevated temperatures. In contrast, herbivorous protist grazing and species-specific growth rates decreased significantly (50%) at +6 °C. This differential response in phytoplankton and herbivores to temperature increases resulted in a decrease of primary production removed with increasing temperature. Phaeocystis spp. abundance was negatively correlated with bulk grazing rate. Growth and grazing rates were variable but showed no evidence of an inherent, low temperature limitation. Herbivorous protist growth rates in this study and in a literature review were comparable to rates from temperate waters. Thus, an inherent physiological inhibition of protistan growth or grazing rates in polar waters is not supported by the data. The large variability between lack of grazing and high rates of primary production removal observed here and confirmed in the literature for polar waters implies larger amplitude fluctuations in phytoplankton biomass than slower, steady grazing losses of primary production.